THE PUBLIC’S ROLE IN DEVELOPING STATE CUSTOMS POLICY: ECONOMIC AND LEGAL ASPECTS - Ivan Yaromiy; Viktor Rekun; Yaroslav Stupnyk (Baltic Journal of Economic Studies)
This research topic examines the role of the public in shaping national customs policy in economic and legal terms. The research aims to analyse the framework of categories and concepts, to study the state of legal regulation and an economic component, and to identify the public role in shaping national customs policy. The methodology employed in this study encompassed a range of approaches to scientific knowledge, including systems analysis, dialectical methods, formal-logical methods, and structural-functional methods. Results. This paper sets out to analyse normative and theoretical approaches to defining the legal category of "state customs policy", and to render the content features of that category. The paper puts forward the argument that the economic component of domestic customs policy should be considered as a set of measures aimed at ensuring the state's economic security, stimulating foreign economic activity, replenishing the state budget, and developing the national economy through the regulation of customs relations. The fundamental components of the economic component of state customs policy are identified, namely: 1) customs regulation; 2) application of non-tariff regulation; 3) customs payments; 4) customs control; 5) promotion of foreign economic activity; 6) protection of the domestic market; 7) economic security. It is important to acknowledge that the public is defined as an active, legitimate, interested, and organised group of individuals and legal entities participating in public life to protect their interests and contribute to the development of society. The author delineates the general features of the legal category "public" as follows: 1) subjectivity (formed from individuals and/or legal entities, their associations, organisations, or groups); 2) legitimacy (activities meet the current legislation of Ukraine); 3) public position and interest in public issues (manifestation of interest and active stance in specific areas of public life, the achievement of specific interests and goals); 4) representation (can be represented by authorised persons acting on its behalf); 5) legal form of organisation (in particular, in the form of public organisations, trade unions, and self-organisation bodies). The economic component of domestic customs policy is predicated on the creation of favourable conditions for foreign economic activity, the protection of national interests, and the replenishment of the state budget. It has been substantiated that the economic component of state customs policy constitutes an important tool for the country's economic development and security. The following forms of public participation in the formation of state customs policy are systematised: public hearings, the functioning of the public council, public consultations, public expertise, citizens' appeals, co-operation with non-governmental organisations, involvement of the latter in monitoring activities of customs authorities, and engagement of public representatives in the work of commissions vested with the formulation and implementation of customs policy. A review of good practices is conducted, with a particular emphasis on the necessity of reinstating the operation of the institution of advisers under the Office of the Head of the State Customs Service of Ukraine and heads of customs.